Sex Differences in Right Ventricular Dysfunction: Insights From the Bench to Bedside - Keen, Jennifer; Prisco, Sasha Z.; Prins, Kurt (Frontiers in Physiology, 2021)
There are inherent distinctions in right ventricular (RV) performance based on sex as females have better RV function than males. These differences are magnified and have very important prognostic implications in two RV-centric diseases, pulmonary hypertension (PH) and arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D). In both PH and ARVC/D, RV dysfunction results in poor patient outcomes. However, there are no currently approved therapies specifically targeting the failing RV, an important unmet need for these two life-threatening disorders. In this review, we highlight human data demonstrating divergent RV phenotypes in healthy, PH, and ARVC/D patients based on sex. Furthermore, we discuss the links between estrogen (the female predominant sex hormone), testosterone (the male predominant sex hormone) and dehydroepiandrosterone (a precursor hormone for multiple sex hormones in males and females) and RV function in both disorders. To provide potential mechanistic insights into sex differences in RV function, we review data that investigate how sex hormones combat or contribute to pathophysiological changes in the RV. Finally, we highlight the ongoing clinical trials in pulmonary arterial hypertension targeting estrogen and dehydroepiandrosterone signaling. Hopefully, a greater understanding of the factors that promote superior RV function in females will lead to novel therapeutic approaches to combat RV dysfunction in PH and ARVC/D.